How much do Cantonese ESL learners know about the English article system?. (February 2016) - Chan, Alice Yin Wa
Abstract: This article investigated Cantonese ESL learners' explicit knowledge of the English article system. A total of 33 Cantonese ESL learners majoring in English participated in a questionnaire survey consisting of both ranking questions and open-ended questions requiring them to give detailed descriptions about their use and knowledge of English articles. The results of the study showed that many respondents were confident of their use of English articles, but they did not regard articles as very important for speaking, reading, writing or listening. They did not possess the metalanguage that enabled them to articulate the functions and semantics of different English articles and had some misconceptions and/or confusion about the system. These misconceptions may be the source of certain article errors, such as substitution errors. It is suggested that formal and systematic teaching be given to enhance ESL learners' explicit knowledge of the English article system and to strengthen their use of English articles.